Fluorine-containing copolymer
By adjusting the monomer unit ratio and melt flow rate of the fluorinated copolymer, a molded body with excellent shape stability, wear resistance, ozone resistance, low carbon dioxide permeability, and durability at high temperatures was prepared, solving the challenge of simultaneously satisfying multiple properties in existing technologies.
Patent Information
- Application Number
- CN202280015021.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-02-26
- Filing Date
- 2022-02-28
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2042-02-28
AI Technical Summary
Existing technologies cannot simultaneously satisfy the requirements of fluoropolymers for shape stability at high temperatures, wear resistance, ozone resistance, low carbon dioxide permeability, and durability, and also cannot easily allow fluoride ions to dissolve into the drug solution.
A fluorinated copolymer containing tetrafluoroethylene, hexafluoropropylene and fluoroalkyl vinyl ether units was used to control the number of functional groups by adjusting the monomer unit ratio and melt flow rate, and the resulting molded body was prepared by extrusion molding.
It achieves molded bodies that are stable in shape at high temperatures, have excellent wear resistance, ozone resistance, low carbon dioxide permeability and durability, and do not easily allow fluoride ions to dissolve into the drug solution.
Smart Images

Figure BDA0004394347770000061 
Figure BDA0004394347770000181 
Figure BDA0004394347770000231
Abstract
Description
Technical Field
[0001] This invention relates to fluorinated copolymers. Background Technology
[0002] Patent Document 1 discloses a multilayer polymer structure comprising at least two adjacent layers of fluoropolymers, characterized in that one of the layers comprises a perfluoroalkoxy polymer and the adjacent layers comprise a fluorinated ethylene-propylene polymer.
[0003] Existing technical documents
[0004] Patent documents
[0005] Patent Document 1: Japanese Patent Publication No. 2001-501551 Summary of the Invention
[0006] The problem that the invention aims to solve
[0007] The purpose of this invention is to provide a fluorinated copolymer that can be used to obtain beautiful tubes through extrusion molding, and can produce molded bodies with excellent wear resistance at 25°C, ozone resistance, low carbon dioxide permeability, rigidity at 75°C, tensile creep resistance at 110°C, excellent durability under repeated loads, and low fluoride ion dissolution into the pharmaceutical solution.
[0008] Methods for solving problems
[0009] According to the present invention, a fluorinated copolymer is provided, which is a fluorinated copolymer containing tetrafluoroethylene units, hexafluoropropylene units, and fluorinated (alkyl vinyl ether) units, wherein the content of hexafluoropropylene units is 11.5% to 12.5% by mass relative to all monomer units, the content of fluorinated (alkyl vinyl ether) units is 0% to 0.5% by mass relative to all monomer units, the melt flow rate at 372°C is 0.8 g / 10 min to 4.0 g / 10 min, and the total number of -CF2H, carbonyl-containing terminal groups, -CF=CF2, and -CH2OH is relative to per 10 6 The number of carbon atoms in the main chain is less than 50.
[0010] The content of fluorinated (alkyl vinyl ether) units is preferably 0 to 0.1% by mass relative to all monomer units.
[0011] The melt flow rate at 372℃ is preferably 1.0 g / 10 min to 3.2 g / 10 min.
[0012] The fluorinated (alkyl vinyl ether) unit is preferably a perfluorinated (propyl vinyl ether) unit.
[0013] In addition, according to the present invention, an extruded or transfer-molded article is provided, which contains the above-mentioned fluorinated copolymer.
[0014] In addition, according to the present invention, a coated wire is provided having a coating layer containing the above-mentioned fluorinated copolymer.
[0015] In addition, according to the present invention, a molded body is provided, which is a molded body containing the above-mentioned fluorinated copolymer, wherein the molded body is a bottle, bag, tube, film or wire coating.
[0016] The effects of the invention
[0017] According to the present invention, a fluorinated copolymer can be provided, which can be used to obtain beautiful tubes by extrusion molding, and can produce molded articles with abrasion resistance at 25°C, ozone resistance, low carbon dioxide permeability, rigidity at 75°C, tensile creep resistance at 110°C, excellent durability under repeated loads, and low fluoride ion dissolution into the pharmaceutical solution. Detailed Implementation
[0018] The specific embodiments of the present invention will be described in detail below, but the present invention is not limited to the following embodiments.
[0019] The fluorinated copolymer of the present invention contains tetrafluoroethylene (TFE) units, hexafluoropropylene (HFP) units, and fluorinated (alkyl vinyl ether) (FAVE) units.
[0020] For bottles containing carbonated water, storage bags for preserving vegetables and fruits in the presence of carbon dioxide, and tubes for supplying carbonated water and carbon dioxide, low carbon dioxide permeability is required. Simultaneously, these molded bodies must maintain shape stability even at high temperatures, be resistant to abrasion, and be durable against disinfectants such as ozone water and hydrogen peroxide. However, fluoropolymers that can simultaneously meet all these requirements are currently unknown.
[0021] Findings: By adjusting the content of HFP and FAVE units, melt flow rate, and number of functional groups in fluorinated copolymers containing TFE, HFP, and FAVE units to extremely limited ranges, the abrasion resistance at 25°C, ozone resistance, low carbon dioxide permeability, rigidity at 75°C, tensile creep resistance at 110°C, and durability under repeated loads of the molded articles obtained from fluorinated copolymers are significantly improved.
[0022] Furthermore, by using extrusion molding to form the fluorinated copolymer of the present invention, a very thick coating layer with uniform thickness can be formed on core wires with very large diameters, resulting in beautiful tubes, and it can be easily molded into films of uniform thickness. Thus, the fluorinated copolymer of the present invention can be used not only as a material for bottles, bags, and tubes, but also for a wide range of applications such as wire coatings and films.
[0023] The fluorinated copolymer of the present invention is a melt-processable fluoropolymer. Melt processability refers to the ability to melt and process the polymer using existing processing equipment such as extruders and injection molding machines.
[0024] As a FAVE that constitutes the above-mentioned FAVE unit, the FAVE can be selected from the general formula (1):
[0025] CF2 = CFO(CF2CFY) 1 O) p -(CF2CF2CF2O) q -Rf (1)
[0026] (where Y) 1 The monomers and general formula (2) are shown below: (where F or CF3 is represented, and Rf represents a perfluoroalkyl group with 1 to 5 carbon atoms. p represents an integer from 0 to 5, and q represents an integer from 0 to 5.)
[0027] CFX = CXOCF2OR 1 (2)
[0028] (In the formula, X being the same or different represents H, F, or CF3, R) 1 The group consisting of at least one monomer, either straight-chain or branched, comprising or not comprising at least one of the atoms selected from the group consisting of H, Cl, Br and I, having a carbon number of 1 to 6, or comprising or not comprising at least one of the atoms selected from the group consisting of H, Cl, Br and I, having a carbon number of 5 or 6.
[0029] Among them, the monomer represented by general formula (1) is preferred as the FAVE, more preferably at least one of the group consisting of perfluoro(methyl vinyl ether), perfluoro(ethyl vinyl ether) (PEVE) and perfluoro(propyl vinyl ether) (PPVE), further preferably at least one of the group consisting of PEVE and PPVE, and particularly preferably PPVE.
[0030] The content of HFP units in fluorinated copolymers is 11.5% to 12.5% by mass relative to all monomer units. If the content of HFP units is too low, it is impossible to obtain molded articles with excellent abrasion resistance and ozone resistance at 25°C. If the content of HFP units is too high, it is impossible to obtain molded articles with excellent rigidity at 75°C, tensile creep resistance at 110°C, and durability under repeated loads.
[0031] The content of FAVE units in the fluorinated copolymer is 0 to 0.5% by mass relative to all monomer units, preferably 0.4% by mass or less, more preferably 0.3% by mass or less, even more preferably 0.2% by mass or less, and still more preferably 0.1% by mass or less. By keeping the content of FAVE units within the above range, it is possible to obtain a molded article with excellent abrasion resistance at 25°C, ozone resistance, low carbon dioxide permeability, rigidity at 75°C, tensile creep resistance at 110°C, and durability under repeated loads. If the content of FAVE units is too high, it is not possible to obtain a molded article with excellent rigidity at 75°C and tensile creep resistance at 110°C.
[0032] The content of TFE units in the fluorinated copolymer is preferably 88.5% by mass or less, more preferably 87.0% by mass or more, more preferably 87.1% by mass or more, even more preferably 87.2% by mass or more, even more preferably 87.3% by mass or more, and particularly preferably 87.4% by mass or more, relative to all monomer units. Alternatively, the content of TFE units can be selected such that the total content of HFP units, FAVE units, TFE units, and other monomer units is 100% by mass.
[0033] The fluorinated copolymer of the present invention only needs to contain the above three monomer units. It can be a copolymer containing only the above three monomer units, or it can be a copolymer containing the above three monomer units and other monomer units.
[0034] As for other monomers, there are no particular limitations as long as they can copolymerize with TFE, HFP, and FAVE. They can be either fluorinated or non-fluorinated monomers.
[0035] As a fluorinated monomer, it is preferably selected from trifluorochloroethylene, vinylidene fluoride, vinylidene fluoride, trifluoroethylene, hexafluoroisobutylene, CH2=CZ. 1 (CF2) n Z 2 (where Z) 1 For H or F, Z 2 The monomers shown are H, F, or Cl, where n is an integer from 1 to 10, CF2=CF-O-CH2-Rf 2 (where Rf) 2 It is at least one of the following groups: alkyl perfluorovinyl ether derivatives (represented by a perfluoroalkyl group having 1 to 5 carbon atoms), perfluoro-2,2-dimethyl-1,3-dioxacyclopentene [PDD], and perfluoro-2-methylene-4-methyl-1,3-dioxacyclopentane [PMD].
[0036] As CH2=CZ 1 (CF2) n Z 2Examples of the monomers shown include CH2=CFCF3, CH2=CH-C4F9, and CH2=CH-C6F. 13 CH2=CF-C3F6H, etc.
[0037] Examples of non-fluorinated monomers include hydrocarbon monomers that can copolymerize with TFE, HFP, and FAVE. Examples of hydrocarbon monomers include: olefins such as ethylene, propylene, butene, and isobutylene; alkyl vinyl ethers such as ethyl vinyl ether, propyl vinyl ether, butyl vinyl ether, isobutyl vinyl ether, and cyclohexyl vinyl ether; vinyl acetate, vinyl propionate, vinyl butyrate, vinyl isobutyrate, vinyl valerate, vinyl pentanoate, vinyl hexanoate, vinyl octanoate, vinyl decanoate, vinyl tert-carbonate, vinyl laurate, vinyl myristate, vinyl palmitate, vinyl stearate, vinyl benzoate, p-tert-butylbenzoate, vinyl cyclohexanecarboxylate, and vinyl monochloroacetate. Vinyl esters such as vinyl adipate, vinyl acrylate, vinyl methacrylate, vinyl crotonate, vinyl sorbate, vinyl cinnamate, vinyl undecenoate, vinyl glycolate, vinyl hydroxypropionate, vinyl hydroxybutyrate, vinyl hydroxyvalerate, vinyl hydroxyisobutyrate, and vinyl hydroxycyclohexanecarboxylate; alkyl allyl ethers such as ethyl allyl ether, propyl allyl ether, butyl allyl ether, isobutyl allyl ether, and cyclohexyl allyl ether; and alkyl allyl esters such as ethyl allyl ester, propyl allyl ester, butyl allyl ester, isobutyl allyl ester, and cyclohexyl allyl ester.
[0038] As non-fluorinated monomers, they can also be hydrocarbon monomers containing functional groups capable of copolymerizing with TFE, HFP, and FAVE. Examples of hydrocarbon monomers containing functional groups include hydroxyalkyl vinyl ethers such as hydroxyethyl vinyl ether, hydroxypropyl vinyl ether, hydroxybutyl vinyl ether, hydroxyisobutyl vinyl ether, and hydroxycyclohexyl vinyl ether; non-fluorinated monomers with glycidyl groups such as glycidyl vinyl ether and glycidyl allyl ether; non-fluorinated monomers with amino groups such as aminoalkyl vinyl ether and aminoalkyl allyl ether; non-fluorinated monomers with amide groups such as (meth)acrylamide and hydroxymethylacrylamide; bromine-containing alkenes, iodine-containing alkenes, bromine-containing vinyl ethers, and iodine-containing vinyl ethers; and non-fluorinated monomers with nitrile groups.
[0039] The content of other monomer units in the fluorinated copolymer of the present invention is preferably 0 to 1.5% by mass, more preferably 1.0% by mass or less, even more preferably 0.5% by mass or less, and particularly preferably 0.1% by mass or less, relative to all monomer units.
[0040] The melt flow rate (MFR) of the fluorinated copolymer is 0.8 g / 10 min to 4.0 g / 10 min, preferably 0.9 g / 10 min or more, more preferably 1.0 g / 10 min or more, preferably 3.8 g / 10 min or less, more preferably 3.6 g / 10 min or less, further preferably 3.5 g / 10 min or less, particularly preferably 3.4 g / 10 min or less, and most preferably 3.2 g / 10 min or less. If the MFR is too low, it is impossible to obtain a molded article with low carbon dioxide permeability and excellent rigidity at 75°C. If the MFR is too high, it is impossible to obtain a molded article with excellent abrasion resistance and ozone resistance at 25°C. In addition, if the MFR is too high, it is impossible to form a film of uniform thickness at high forming speed by extrusion molding.
[0041] In this invention, the melt flow rate is the value obtained according to ASTM D-1238 using a melt flow index tester G-01 (manufactured by Toyo Seiki Co., Ltd.) as the mass (g / 10 min) of polymer flowing out of a die with an inner diameter of 2 mm and a length of 8 mm every 10 minutes under a load of 5 kg at 372 °C.
[0042] MFR can be adjusted by modifying the type and amount of polymerization initiator and the type and amount of chain transfer agent used in monomer polymerization.
[0043] 10 of fluorinated copolymers 6 The total number of -CF2H, carbonyl-containing terminal groups, -CF=CF2, and -CH2OH groups per main chain carbon atom is 50 or less. The preferred order of the total number of these functional groups is 40 or less, 30 or less, 25 or less, and less than 21. By ensuring the total number of these functional groups is within the above range, it is possible to obtain a molded body with excellent ozone resistance and that does not easily leach fluoride ions into solutions such as hydrogen peroxide.
[0044] The carbonyl-containing terminal groups are, for example, -COF, -COOH, -COOR (R is alkyl), -CONH2, and -O(C=O)OR (R is alkyl). The type of alkyl group (R) in -COOR and -O(C=O)OR is determined by the polymerization initiator, chain transfer agent, etc. used in the manufacture of fluorinated copolymers, and is, for example, alkyl groups with 1 to 6 carbon atoms such as -CH3.
[0045] The identification of the types of functional groups and the determination of the number of functional groups mentioned above can be achieved using infrared spectroscopy.
[0046] Regarding the number of functional groups, specifically, it was determined using the following method. First, the above-mentioned fluorinated copolymer was cold-pressed to produce a film with a thickness of 0.25 mm to 0.30 mm. The film was analyzed by Fourier transform infrared spectroscopy to obtain the infrared absorption spectrum of the above-mentioned fluorinated copolymer, and a differential spectrum was obtained compared with the background spectrum of a fully fluorinated copolymer without functional groups. The number of functional groups in the above-mentioned fluorinated copolymer was calculated from the absorption peaks of specific functional groups shown in the differential spectrum according to the following formula (A). 6 The number of functional groups N per carbon atom.
[0047] N = I × K / t (A)
[0048] I: Absorbance
[0049] K: Correction coefficient
[0050] t: Membrane thickness (mm)
[0051] For reference, the absorption frequencies, molar absorptivity, and correction factors for some functional groups are shown in Table 1. Furthermore, the molar absorptivity was determined using FT-IR measurements of low-molecular-weight model compounds.
[0052] [Table 1]
[0053] Table 1
[0054]
[0055] The absorption frequencies of -CH2CF2H, -CH2COF, -CH2COOH, -CH2COOCH3, and -CH2CONH2 are tens of Kaiser (cm) lower than those of -CF2H, -COF, free -COOH, and bonded -COOH, -COOCH3, and -CONH2, respectively, as shown in the table. -1 ).
[0056] For example, the number of functional groups in -COF refers to the number of functional groups originating from the absorption frequency of -CF2COF, which is 1883 cm⁻¹. -1 The number of functional groups derived from the absorption peak at 1840 cm⁻¹ and the absorption frequency originating from -CH₂COF were also analyzed. -1 The total number of functional groups obtained from the absorption peak at the given location.
[0057] Alternatively, the number of -CF2H groups can also be determined using a nuclear magnetic resonance (NMR) apparatus. The measurement temperature is set to (the melting point of the polymer + 20) °C, and 19F-NMR is performed. The result is obtained from the peak integral value of the -CF2H groups.
[0058] Functional groups such as the -CF2H group are functional groups present at the ends of the main chain or side chains of fluorinated copolymers, and functional groups present in the main chain or side chains. These functional groups are introduced into fluorinated copolymers, for example, through chain transfer agents or polymerization initiators used in the manufacture of the copolymers. For example, when an alcohol is used as a chain transfer agent, or when a peroxide having a -CH2OH structure is used as a polymerization initiator, -CH2OH is introduced to the ends of the main chain of the fluorinated copolymer. Alternatively, these functional groups are introduced to the ends of the side chains of the fluorinated copolymer by polymerizing monomers containing these functional groups.
[0059] By subjecting the fluorinated copolymer having such functional groups to wet heat treatment, fluorination treatment, or other treatments, a fluorinated copolymer having the number of functional groups within the aforementioned range can be obtained. The fluorinated copolymer of the present invention preferably underwent wet heat treatment or fluorination treatment, and more preferably fluorination treatment. The fluorinated copolymer of the present invention also preferably has a -CF3 terminal group.
[0060] The melting point of the fluorinated copolymer is preferably 220°C to 290°C, more preferably 240°C to 280°C. By keeping the melting point within the above range, beautiful tubes can be obtained by extrusion molding, and molded articles with superior abrasion resistance at 25°C, ozone resistance, low carbon dioxide permeability, rigidity at 75°C, tensile creep resistance at 110°C, and durability under repeated loads can be obtained.
[0061] In this invention, the melting point can be determined using a differential scanning calorimeter (DSC).
[0062] The carbon dioxide permeability coefficient of the fluorinated copolymer is preferably 1800 cm⁻¹. 3 ·mm / (m 2 The fluorinated copolymer of the present invention exhibits excellent low carbon dioxide permeability due to appropriate adjustments to the content of HFP units, the content of FAVE units, the melt flow rate (MFR), and the number of functional groups.
[0063] In this invention, the carbon dioxide transmission coefficient can be determined under test conditions of 70°C and 0% RH. The specific determination of the carbon dioxide transmission coefficient can be performed using the methods described in the examples.
[0064] The amount of fluoride ions dissolved in hydrogen peroxide water by the fluoride-containing copolymer of the present invention is preferably 4.0 ppm or less by mass, more preferably 3.0 ppm or less, and even more preferably 2.8 ppm or less. By keeping the amount of fluoride ions dissolved within the above range, even when bottles and bags made using the fluoride-containing copolymer of the present invention are vigorously washed or disinfected with hydrogen peroxide water, fluoride ions will not be dissolved.
[0065] In this invention, the immersion test in hydrogen peroxide water can be carried out as follows: using a fluorinated copolymer, a test piece with a weight equivalent to 10 molded pieces (15mm×15mm×0.2mm) is prepared. A polypropylene bottle containing the test piece and 15g of 3% hydrogen peroxide aqueous solution is placed in a constant temperature bath at 95°C and left for 20 hours.
[0066] The fluorinated copolymers of the present invention can be manufactured by any of the polymerization methods such as bulk polymerization, solution polymerization, suspension polymerization, and emulsion polymerization. In these polymerization methods, the conditions such as temperature and pressure, the polymerization initiator, chain transfer agent, solvent, and other additives can be appropriately set according to the desired composition and amount of the fluorinated copolymer.
[0067] Oil-soluble free radical polymerization initiators or water-soluble free radical initiators can be used as polymerization initiators.
[0068] As an oil-soluble free radical polymerization initiator, it can be a known oil-soluble peroxide, and the following substances can be cited as representative examples:
[0069] Dialkyl percarbonate esters, such as di-n-propyl percarbonate, diisopropyl percarbonate, and disec-butyl percarbonate;
[0070] Peroxide esters such as tert-butyl peroxide isobutyrate and tert-butyl perpentyl peroxide;
[0071] Dialkyl peroxides such as di-tert-butyl peroxide;
[0072] Di[fluoro(or fluorochloro)acyl] peroxides; etc.
[0073] Examples of diacyl peroxides include those represented by [(RfCOO)-]2 (where Rf is a perfluoroalkyl, ω-hydroperfluoroalkyl, or fluorochloroalkyl).
[0074] Examples of di[fluoro(or fluorochloro)acyl]peroxides include, for example, di(ω-hydro-dodecanoyl)peroxide, di(ω-hydro-tetradecanoyl)peroxide, di(ω-hydro-hexadecanoyl)peroxide, di(perfluorobutyryl)peroxide, di(perfluoropentanoyl)peroxide, di(perfluorohexanoyl)peroxide, di(perfluoroheptanoyl)peroxide, di(perfluorooctanoyl)peroxide, di(perfluorononanoyl)peroxide, di(ω-chloro-hexafluorobutyryl)peroxide, di(ω-chloro-decanoyl)peroxide, and di(ω-decanoyl)peroxide. Fluorohexyl peroxide, di(ω-chloro-tetrafluorooctanoyl) peroxide, ω-hydro-dodecanoyl-ω-hydrohexadecanoyl-peroxide, ω-chloro-hexafluorobutyryl-ω-chloro-decafluorohexanoyl-peroxide, ω-hydro-dodecanoyl-perfluorobutyryl-peroxide, di(dichloropentafluorobutyryl) peroxide, di(trichlorooctafluorohexanoyl) peroxide, di(tetrachloroundecanoyl) peroxide, di(pentachlorotetrafluorodecanoyl) peroxide, di(undecatrifluorotetrafluorodienoyl) peroxide, etc.
[0075] As a water-soluble free radical polymerization initiator, it can be a known water-soluble peroxide, such as ammonium salts, potassium salts, sodium salts of persulfate, perboric acid, perchloric acid, superphosphoric acid, and percarbonate, as well as tert-butyl maleate peroxide and tert-butyl hydroperoxide. It may also contain reducing agents such as sulfites, in amounts ranging from 0.1 to 20 times that of the peroxide.
[0076] If an oil-soluble free radical polymerization initiator is used as the polymerization initiator, the generation of -COF and -COOH can be avoided, and the total number of -COF and -COOH in the fluorinated copolymer can be easily adjusted to the above-mentioned range, which is therefore preferred. Furthermore, if an oil-soluble free radical polymerization initiator is used, it also tends to easily adjust the total number of -CF2H, carbonyl-containing terminal groups, -CF=CF2, and -CH2OH to the above-mentioned range. In particular, it is preferable to manufacture the fluorinated copolymer by suspension polymerization using an oil-soluble free radical polymerization initiator. As an oil-soluble free radical polymerization initiator, at least one is preferably selected from the group consisting of dialkyl percarbonate esters and di[fluoro(or fluorochloro)acyl]peroxides, more preferably at least one is selected from the group consisting of di-n-propyl percarbonate, diisopropyl percarbonate, and di(ω-hydro-dodecylfluoroheptyl)peroxide.
[0077] Examples of chain transfer agents include hydrocarbons such as ethane, isopentane, n-hexane, and cyclohexane; aromatics such as toluene and xylene; ketones such as acetone; acetates such as ethyl acetate and butyl acetate; alcohols such as methanol, ethanol, and 2,2,2-trifluoroethanol; thiols such as methyl mercaptan; halogenated hydrocarbons such as carbon tetrachloride, chloroform, dichloromethane, and chloromethane; and 3-fluorobenzotrifluoride. The amount added varies depending on the chain transfer constant of the compound used, and is typically used in the range of 0.01 to 20 parts by mass relative to 100 parts by mass of solvent.
[0078] For example, when using dialkyl peroxide carbonates, di[fluoro(or fluorochloro)acyl]peroxides, etc., as polymerization initiators, the resulting fluorinated copolymers have excessively high molecular weights, sometimes making it difficult to adjust to the desired melt flow rate. However, chain transfer agents can be used to adjust the molecular weight. Fluorinated copolymers are particularly preferably manufactured by suspension polymerization using chain transfer agents such as alcohols and oil-soluble free radical polymerization initiators.
[0079] Examples of solvents include water and mixtures of water and alcohol. Alternatively, the monomers used in the polymerization of the fluorinated copolymers of this invention can also be used as solvents.
[0080] In suspension polymerization, fluorinated solvents can be used in addition to water. Examples of fluorinated solvents include hydrochlorofluorocarbons such as CH3CClF2, CH3CCl2F, CF3CF2CCl2H, and CF2ClCF2CFHCl; chlorofluorocarbons such as CF2ClCFClCF2CF3 and CF3CFClCFClCF3; and perfluoroalkyl hydrocarbons such as perfluorocyclobutane, CF3CF2CF2CF3, CF3CF2CF2CF2CF3, and CF3CF2CF2CF2CF2CF3, with perfluoroalkyl hydrocarbons being preferred. From the perspectives of suspension performance and economy, the amount of fluorinated solvent used is preferably 10 to 100 parts by mass relative to 100 parts by mass of the solvent.
[0081] There is no particular limitation on the polymerization temperature, which can be 0 to 100°C. However, if the decomposition rate of the polymerization initiator is too fast, such as when using dialkyl peroxide carbonate, di[fluoro(or fluorochloro)acyl]peroxide, etc., as the polymerization initiator, it is preferable to use a lower polymerization temperature, such as a polymerization temperature range of 0°C to 35°C.
[0082] The polymerization pressure is appropriately determined based on the type and amount of solvent used, vapor pressure, polymerization temperature, and other polymerization conditions, and is typically 0–9.8 MPaG. The polymerization pressure is preferably 0.1 MPaG–5 MPaG, more preferably 0.5 MPaG–2 MPaG, and even more preferably 0.5 MPaG–1.5 MPaG. Furthermore, a polymerization pressure of 1.5 MPaG or higher can improve production efficiency.
[0083] Examples of additives used in polymerization include suspension stabilizers. There are no particular limitations on existing, well-known suspension stabilizers; methylcellulose, polyvinyl alcohol, etc., can be used. When a suspension stabilizer is used, the suspended particles generated by the polymerization reaction are stably dispersed in the aqueous medium. Therefore, even when using a SUS-made reaction tank without anti-adhesion treatment such as a glass liner, the suspended particles are less likely to adhere to the reaction tank. This allows the use of a high-pressure-resistant reaction tank, enabling polymerization under high pressure and improving production efficiency. Conversely, if polymerization is carried out without a suspension stabilizer, and a SUS-made reaction tank without anti-adhesion treatment is used, suspended particles may adhere, reducing production efficiency. The concentration of the suspension stabilizer relative to the aqueous medium can be adjusted appropriately according to the conditions.
[0084] When an aqueous dispersion containing a fluoropolymer is obtained through polymerization, the dried fluoropolymer can be recovered by precipitating, washing, and drying the fluoropolymer contained in the aqueous dispersion. Alternatively, when a fluoropolymer is obtained in slurry form through polymerization, the dried fluoropolymer can be recovered by removing the slurry from the reaction vessel and washing and drying it. Drying allows the fluoropolymer to be recovered in powder form.
[0085] Fluorinated copolymers obtained through polymerization can be granulated. There are no particular limitations on the granulation method; existing known methods can be used. For example, methods such as melt extruding the fluorinated copolymer using a single-screw extruder, twin-screw extruder, or tandem extruder, and then cutting it into granules of a specified length, can be used. The extrusion temperature during melt extrusion needs to be varied depending on the melt viscosity of the fluorinated copolymer and the manufacturing method; preferably, it is between the melting point of the fluorinated copolymer and 20°C to 140°C. There are no particular limitations on the cutting method of the fluorinated copolymer; existing known methods such as wire cutting, thermal cutting, underwater cutting, and sheet cutting can be used. The volatile components in the granules can also be removed by heating (degassing treatment). Alternatively, the granules can be treated by contacting them with warm water at 30°C to 200°C, steam at 100°C to 200°C, or hot air at 40°C to 200°C.
[0086] Fluorinated copolymers obtained through polymerization can also be heated to temperatures above 100°C in the presence of air and water (wetting heat treatment). Examples of wetting heat treatment methods include: using an extruder, supplying air and water while melting and extruding the fluorinated copolymer obtained through polymerization. Wetting heat treatment can convert thermally unstable functional groups such as -COF and -COOH in the fluorinated copolymer into the more thermally stable -CF2H, and can easily adjust the total number of -CF2H, carbonyl-containing terminal groups, -CF=CF2, and -CH2OH in the fluorinated copolymer to the aforementioned range. Besides air and water, heating the fluorinated copolymer in the presence of an alkali metal salt can promote the conversion reaction to -CF2H. However, it should be noted that contamination from alkali metal salts should be avoided depending on the intended use of the fluorinated copolymer.
[0087] Fluorinated copolymers obtained by polymerization can also be fluorinated. From the perspective of obtaining molded bodies that do not easily leach fluoride ions into solutions such as hydrogen peroxide, fluorination of the fluorinated copolymer is preferred. Fluorination can be carried out by contacting the unfluorinated fluorinated copolymer with a fluorinated compound. Through fluorination, thermally unstable functional groups such as -COOH, -COOCH3, -CH2OH, -COF, -CF=CF2, and -CONH2, as well as thermally stable functional groups such as -CF2H, can be converted into extremely thermally stable -CF3. As a result, the total number of -CF2H, carbonyl-containing terminal groups, -CF=CF2, and -CH2OH groups in the fluorinated copolymer can be easily adjusted to the aforementioned range.
[0088] As for fluorine-containing compounds, there are no particular limitations; any fluorine radical source that generates fluorine radicals under fluorination conditions can be cited. Examples of such fluorine radical sources include F2 gas, CoF3, AgF2, UF6, OF2, N2F2, CF3OF, and fluorinated halogens (e.g., IF5, ClF3).
[0089] Fluorine radical sources such as F2 gas can be 100% concentrated, but from a safety perspective, it is preferable to mix them with an inert gas and dilute them to 5% to 50% by mass before use, and more preferably to 15% to 30% by mass. Examples of such inert gases include nitrogen, helium, and argon; from an economic perspective, nitrogen is preferred.
[0090] The conditions for fluorination are not particularly limited; the molten fluorinated copolymer can be brought into contact with the fluorinated compound. However, it is generally carried out at a temperature below the melting point of the fluorinated copolymer, preferably between 20°C and 220°C, and more preferably between 100°C and 200°C. The fluorination treatment is typically carried out for 1 hour to 30 hours, preferably 5 hours to 25 hours. The preferred method of fluorination treatment is to bring the unfluorinated fluorinated copolymer into contact with fluorine gas (F2 gas).
[0091] The fluorinated copolymer of the present invention can also be mixed with other components as needed to obtain a composition. Other components include fillers, plasticizers, processing aids, mold release agents, pigments, flame retardants, lubricants, light stabilizers, weather stabilizers, conductive agents, antistatic agents, ultraviolet absorbers, antioxidants, foaming agents, fragrances, oils, softeners, defluorinated hydrogen agents, etc.
[0092] Examples of fillers include silica, kaolin, clay, organoclay, talc, mica, alumina, calcium carbonate, calcium terephthalate, titanium dioxide, calcium phosphate, calcium fluoride, lithium fluoride, cross-linked polystyrene, potassium titanate, carbon, boron nitride, carbon nanotubes, and glass fiber. Examples of conductive agents include carbon black. Examples of plasticizers include dioctyl phthalate and pentaerythritol. Examples of processing aids include carnauba wax, sulfone compounds, low molecular weight polyethylene, and fluorinated additives. Examples of defluorinating agents include organonium and amidines.
[0093] In addition, other polymers besides the fluorinated copolymers mentioned above can also be used as other components. Examples of other polymers include fluoropolymers, fluororubbers, and non-fluorinated polymers, in addition to the fluorinated copolymers mentioned above.
[0094] Examples of methods for manufacturing the above composition include: dry mixing of the fluorinated copolymer with other components; pre-mixing the fluorinated copolymer with other components using a mixer, followed by melt mixing using a kneader, melt extruder, etc.; etc.
[0095] The fluorinated copolymers or the above-described compositions of the present invention can be used as processing aids, molding materials, etc., and are preferably used as molding materials. Additionally, aqueous dispersions, solutions, suspensions, and copolymer / solvent systems of the fluorinated copolymers of the present invention can be used as coatings, or for encapsulation, impregnation, and film casting. However, due to the aforementioned properties, the fluorinated copolymers of the present invention are preferably used as the above-described molding materials.
[0096] The fluorinated copolymer of the present invention or the above composition can also be molded to obtain a molded body.
[0097] The method for molding the above-mentioned fluorinated copolymer or composition is not particularly limited, and examples include injection molding, extrusion molding, compression molding, blow molding, transfer molding, rotational molding, and roll forming. Among these molding methods, extrusion molding, compression molding, or transfer molding are preferred, and extrusion molding or transfer molding is more preferred because it allows for high-productivity production of the molded body; extrusion molding is even more preferred. That is, as the molded body, an extruded molded body, a compression molded body, an injection molded body, or a transfer molded body is preferred, and extruded molded bodies are even more preferred because they allow for high-productivity production; extruded molded bodies are even more preferred. By molding the fluorinated copolymer of the present invention using extrusion molding or transfer molding, a beautiful molded body can be obtained.
[0098] As molded bodies containing the fluorinated copolymer of the present invention, they can be, for example, nuts, bolts, joints, membranes, bottles, washers, wire sheaths, tubes, hoses, pipes, valves, plates, seals, gaskets, cans, rollers, containers, stopcocks, connectors, filter housings, filter covers, flow meters, pumps, wafer carriers, wafer boxes, etc.
[0099] The fluorinated copolymers, the above-described compositions, or the above-described molded articles of the present invention can be used for, for example, the following applications.
[0100] Food packaging films, lining materials for fluid transport pipelines used in food manufacturing processes, gaskets, sealing materials, thin sheets, and other fluid transport components for food manufacturing equipment;
[0101] Chemical stoppers, packaging films, lining materials for fluid delivery pipelines used in chemical manufacturing processes, gaskets, sealing materials, thin plates, and other reagent delivery components;
[0102] Inner lining components for chemical equipment and semiconductor plants' liquid tanks and piping;
[0103] O-rings / pipes / gaskets, valve core materials, hoses, sealing materials, etc. used in the fuel system and peripheral devices of automobiles; hoses, sealing materials, and other fuel delivery components used in the AT system of automobiles.
[0104] The carburetor flange gaskets, shaft seals, valve stem seals, sealing materials, hoses, etc. used in the engine and peripheral devices of automobiles; brake hoses, air conditioning hoses, radiator hoses, wire sheathing materials, and other automobile components.
[0105] O-rings, tubes, gaskets, valve core materials, hoses, sealing materials, rollers, washers, diaphragms, connectors and other chemical delivery components for semiconductor manufacturing equipment;
[0106] Coating and ink components for coating equipment, such as coating rollers, hoses, tubes, and ink containers;
[0107] Food and beverage conduits, hoses, belts, gaskets, connectors and other food and beverage conveying components, food packaging materials, and glass cooking equipment;
[0108] Pipes, hoses, and other components used for waste liquid transportation;
[0109] Pipes, hoses, and other components used for high-temperature liquid transfer;
[0110] Pipes, hoses and other steam piping components used in steam piping;
[0111] Corrosion-resistant tape for piping, such as tape wrapped around the piping on the deck of a ship;
[0112] Various coating materials, such as wire coating materials, optical fiber coating materials, transparent surface coating materials and backing agents applied to the light incident side of photovoltaic elements in solar cells;
[0113] The diaphragm and various sliding components such as gaskets in a diaphragm pump;
[0114] Weather-resistant covers for agricultural films, various roofing materials, and sidewalls;
[0115] Interior materials used in the construction industry, and glass-like covering materials such as non-combustible fire-resistant safety glass;
[0116] Lining materials such as laminated steel sheets used in the home appliance industry.
[0117] Further examples of fuel delivery components used in the fuel systems of the aforementioned automobiles include fuel hoses, filler hoses, and evaporator hoses. These fuel delivery components can also be used for fuels resistant to acidic gasoline, alcohol-based fuels, and fuels containing gasoline additives such as those resistant to methyl tert-butyl ether and amines.
[0118] The aforementioned chemical stoppers and packaging films exhibit excellent chemical resistance to acids and other chemicals. Additionally, anti-corrosion tape wrapped around the piping of chemical equipment can also be cited as a component for transporting the aforementioned chemical solutions.
[0119] Examples of the aforementioned molded bodies include automobile radiator water chambers, medicine tanks, bellows, partitions, rollers, gasoline tanks, waste liquid conveying containers, high-temperature liquid conveying containers, and fish farming and aquaculture tanks.
[0120] Further examples of the molded bodies mentioned above include components used in automobile bumpers, door panels, dashboards, food processing devices, cooking machines, waterproof and oil-proof glass, lighting-related instruments, indicator panels and housings of OA instruments, electrically illuminated signboards, displays, LCD screens, mobile phones, printer chassis, electrical and electronic components, groceries, trash cans, bathtubs, prefabricated bathrooms, exhaust fans, lighting frames, etc.
[0121] Molded articles containing the fluorinated copolymer of the present invention exhibit excellent abrasion resistance at 25°C, ozone resistance, low carbon dioxide permeability, rigidity at 75°C, tensile creep resistance at 110°C, and durability under repeated loads, making them suitable for use in bottles, bags, tubes, films, or wire coatings.
[0122] Molded articles containing the fluorinated copolymers of the present invention are suitable for use as compressed components such as gaskets and seals. The compressed components of the present invention can be gaskets or seals.
[0123] The size and shape of the compressed member of the present invention can be appropriately set according to the application and are not particularly limited. The shape of the compressed member of the present invention can be, for example, ring-shaped. In addition, the compressed member of the present invention can have a circular, elliptical, or quadrilateral shape with rounded corners when viewed from above, and has a through hole in its central part.
[0124] The compressed member of the present invention is preferably used as a component for constructing a non-aqueous electrolyte battery. The compressed member of the present invention is particularly suitable as a component used in a state of contact with the non-aqueous electrolyte in a non-aqueous electrolyte battery. That is, the compressed member of the present invention can have a liquid-contacting surface for contact with the non-aqueous electrolyte in a non-aqueous electrolyte battery.
[0125] As for non-aqueous electrolyte batteries, there are no particular limitations as long as the battery contains a non-aqueous electrolyte; examples include lithium-ion secondary batteries and lithium-ion capacitors. Furthermore, components constituting non-aqueous electrolyte batteries include sealing components and insulating components.
[0126] The non-aqueous electrolyte is not particularly limited and can be one or more of the following known solvents: propylene carbonate, ethylene carbonate, butyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl carbonate, diethyl carbonate, and methyl ethyl carbonate. The non-aqueous electrolyte battery may further include an electrolyte. The electrolyte is not particularly limited and can be LiClO4, LiAsF6, LiPF6, LiBF4, LiCl, LiBr, CH3SO3Li, CF3SO3Li, cesium carbonate, etc.
[0127] The compressed component of the present invention can preferably be used as a sealing component such as a sealing gasket or sealing pad, or an insulating component such as an insulating gasket or insulating pad. A sealing component is used to prevent leakage of liquid or gas or intrusion of liquid or gas from the outside. An insulating component is used for electrical insulation. The compressed component of the present invention can also be used for both sealing and insulation purposes.
[0128] The compressed member of the present invention is suitable for use as a sealing member or an insulating member for non-aqueous electrolyte batteries. Furthermore, the compressed member of the present invention, due to containing the aforementioned fluorinated copolymer, exhibits excellent insulating properties. Therefore, when the compressed member of the present invention is used as an insulating member, it securely seals with two or more conductive members, preventing short circuits over a long period.
[0129] The fluorinated copolymer of the present invention is suitable for use as a material for forming wire coatings. Wires having a coating layer containing the fluorinated copolymer of the present invention exhibit almost no change in outer diameter, thus resulting in excellent electrical properties.
[0130] The coated wire has a core wire and a coating layer disposed around the core wire containing the fluorinated copolymer of the present invention. For example, the coating layer can be an extruded body formed by melt extrusion molding of the fluorinated copolymer of the present invention onto the core wire. The coated wire is suitable for LAN cables (Ethernet cables), high-frequency transmission cables, flat cables, heat-resistant cables, etc., and is particularly suitable for transmission cables such as LAN cables (Ethernet cables) and high-frequency transmission cables.
[0131] The core wire material can be a metallic conductor such as copper or aluminum. The core wire diameter is preferably 0.02 mm to 3 mm. More preferably, the core wire diameter is 0.04 mm or more, even more preferably 0.05 mm or more, and particularly preferably 0.1 mm or more. Even more preferably, the core wire diameter is 2 mm or less.
[0132] Specific examples of core wires include AWG (American wire gauge)-46 (solid copper wire with a diameter of 40μm), AWG-26 (solid copper wire with a diameter of 404μm), AWG-24 (solid copper wire with a diameter of 510μm), and AWG-22 (solid copper wire with a diameter of 635μm).
[0133] The thickness of the coating layer is preferably 0.1 mm to 3.0 mm. The thickness of the coating layer is also preferably less than 2.0 mm.
[0134] Coaxial cables are an example of high-frequency transmission cables. Coaxial cables typically have a structure consisting of an inner conductor, an insulating sheath, an outer conductor layer, and a protective sheath layer layered sequentially from the core to the outer periphery. Molded bodies containing the fluorinated copolymer of the present invention can be suitable as insulating sheaths containing the fluorinated copolymer. The thickness of each layer in the above structure is not particularly limited; typically, the diameter of the inner conductor is about 0.1 mm to 3 mm, the thickness of the insulating sheath is about 0.3 mm to 3 mm, the thickness of the outer conductor layer is about 0.5 mm to 10 mm, and the thickness of the protective sheath is about 0.5 mm to 2 mm.
[0135] The coating may contain air bubbles, which are preferably evenly distributed in the coating.
[0136] The average bubble diameter is not limited, but is preferably 60 μm or less, more preferably 45 μm or less, even more preferably 35 μm or less, even more preferably 30 μm or less, particularly preferably 25 μm or less, and especially preferably 23 μm or less. Furthermore, the average bubble diameter is preferably 0.1 μm or more, more preferably 1 μm or more. The average bubble diameter can be obtained by acquiring an electron microscope image of the wire cross-section, calculating the diameter of each bubble using image processing, and then averaging the results.
[0137] The foaming rate of the coating layer can be 20% or more. More preferably, it is 30% or more, further preferably 33% or more, and even more preferably 35% or more. There is no particular upper limit, for example, 80%. The upper limit of the foaming rate can be 60%. The foaming rate is calculated as ((specific gravity of wire coating material - specific gravity of coating layer) / specific gravity of wire coating material) × 100. The foaming rate can be adjusted appropriately according to the application, for example, by adjusting the gas insertion amount in the extruder described later, or by selecting the type of dissolved gas.
[0138] The coated wire may also have other layers between the core wire and the coating layer, and may further have other layers (outer layers) around the coating layer. If the coating layer contains air bubbles, the wire of the present invention may also be a two-layer structure (outer sheath-foam) with a non-foamed layer inserted between the core wire and the coating layer; a two-layer structure (foam-outer sheath) with a non-foamed layer on the outer layer; and a three-layer structure (outer sheath-foam-outer sheath) with a non-foamed layer on the outer layer of the outer sheath-foam. The non-foamed layer is not particularly limited and may be a resin layer composed of TFE / HFP copolymers, TFE / PAVE copolymers, TFE / ethylene copolymers, vinylidene fluoride polymers, polyolefin resins such as polyethylene [PE], and resins such as polyvinyl chloride [PVC].
[0139] Coated wires can be manufactured, for example, by heating a fluorinated copolymer using an extruder and extruding it onto the core wire while the fluorinated copolymer is in a molten state to form a coating.
[0140] During the formation of the coating layer, the fluorinated copolymer can also be heated, and a gas can be introduced into the fluorinated copolymer while it is in a molten state to form the aforementioned coating layer containing bubbles. The gas can be, for example, dichlorofluoromethane, nitrogen, carbon dioxide, or a mixture of these gases. The gas can be introduced into the heated fluorinated copolymer as a pressurized gas, or it can be generated by mixing a chemical foaming agent into the fluorinated copolymer. The gas dissolves in the molten fluorinated copolymer.
[0141] In addition, the fluorinated copolymer of the present invention is suitable for use as a material in products for high-frequency signal transmission.
[0142] As for the aforementioned high-frequency signal transmission products, there are no particular limitations as long as the product is used for high-frequency signal transmission. Examples include (1) molded boards such as insulating boards for high-frequency circuits, insulating materials for connecting components, and printed wiring boards; (2) molded bodies such as bases and radomes for high-frequency vacuum tubes; and (3) covered wires such as coaxial cables and LAN cables. The aforementioned high-frequency signal transmission products are suitable for use in satellite communication equipment, mobile phone base stations, and other equipment that utilizes microwaves, especially microwaves from 3 GHz to 30 GHz.
[0143] In the above-mentioned high-frequency signal transmission products, the fluorinated copolymer of the present invention is suitable for use as an insulator from the perspective of low dielectric loss tangent.
[0144] As for the molded plate described in (1) above, a printed wiring substrate is preferred from the perspective of obtaining good electrical characteristics. There are no particular limitations on the printed wiring substrate described above; examples include printed wiring substrates for electronic circuits in mobile phones, various computers, and communication devices. As for the molded body described in (2) above, an antenna radome is preferred from the perspective of low dielectric loss.
[0145] The fluorinated copolymers of the present invention are suitable for use in membranes.
[0146] The film of the present invention is useful as a release film. The release film can be manufactured by molding the fluorinated copolymer of the present invention through melt extrusion molding, calendering, compression molding, casting, etc. From the viewpoint of obtaining a uniform film, the release film can be manufactured by melt extrusion molding.
[0147] The membrane of this invention can be applied to the surface of rollers used in OA equipment. Furthermore, the fluorinated copolymer of this invention can be molded into necessary shapes, such as sheets, films, or tubes, through extrusion molding, compression molding, or pressing, for use as a surface material for OA equipment rollers or belts. In particular, thin-walled tubes and membranes can be manufactured using melt extrusion molding.
[0148] The fluorinated copolymers of the present invention are also suitable for use in tubes, bottles, etc.
[0149] The embodiments have been described above, but it is understood that various changes can be made to the methods and details without departing from the spirit and scope of the claims.
[0150] Example
[0151] Next, embodiments will be given to illustrate the implementation of the present invention, but the present invention is not limited to the embodiments described herein.
[0152] The values in the examples were measured using the following methods.
[0153] (Monomer content)
[0154] The content of each monomer unit in the fluorinated copolymer was determined using an NMR analyzer (e.g., Bruker BioSpin, AVANCE300 high-temperature probe) or an infrared absorption analyzer (Perkin Elmer, Spectrum One).
[0155] (Mel flow rate (MFR))
[0156] Regarding the MFR of fluorinated copolymers, according to ASTM D-1238, the mass (g / 10 min) of polymer flowing out of a die with an inner diameter of 2 mm and a length of 8 mm is measured every 10 minutes using a melt flow index tester G-01 (manufactured by Toyo Seiki Co., Ltd.) at 372°C and a load of 5 kg, and the MFR is calculated accordingly.
[0157] (Quantity of -CF2H)
[0158] The number of -CF2H groups in the fluorinated copolymer was determined using an AVANCE-300 nuclear magnetic resonance (NMR) system (manufactured by Bruker BioSpin) at a temperature set to (polymer melting point + 20) °C. 19 The value was determined by F-NMR analysis and obtained from the peak integral of the -CF2H group.
[0159] (The number of -COOH, -COOCH3, -CH2OH, -COF, -CF=CF2, -CONH2)
[0160] The dried powders or granules obtained in the examples and comparative examples were cold-pressed to form films with a thickness of 0.25 mm to 0.3 mm. The films were analyzed by scanning them 40 times using a Fourier transform infrared spectroscopy (FT-IR) device (Spectrum One, PerkinElmer) to obtain infrared absorption spectra. The obtained infrared absorption spectra were compared with those of known films to determine the types of terminal groups. Furthermore, based on the absorption peaks of specific functional groups appearing in the differential spectrum between the obtained infrared absorption spectra and those of known films, the concentration of each 1 × 10⁻⁶ functional group in the sample was calculated according to the following formula (A). 6 The number of functional groups N per carbon atom.
[0161] N = I × K / t (A)
[0162] I: Absorbance
[0163] K: Correction coefficient
[0164] t: Membrane thickness (mm)
[0165] For reference, the absorption frequencies, molar absorptivity, and correction factors for the functional groups in the examples are shown in Table 2. Furthermore, the molar absorptivity was determined using FT-IR measurement data from the low-molecular-weight model compounds.
[0166] [Table 2]
[0167] Table 2
[0168]
[0169] (the number of -OC(=O)OR(carbonate groups))
[0170] Analysis was performed using the method described in International Publication No. 2019 / 220850. The absorption frequency was set to 1817 cm⁻¹. -1 The molar absorbance coefficient was set to 170 (l / cm / mol), and the correction coefficient was set to 1426. Otherwise, the number of -OC(=O)OR (carbonate groups) was calculated in the same way as the number of functional groups N.
[0171] (Melting point)
[0172] Regarding the melting point of the fluorinated copolymer, a differential scanning calorimeter (trade name: X-DSC7000, manufactured by Hitachi High-Tech Science) was used to perform a first heating from 200°C to 350°C at a heating rate of 10°C / min. Then, the temperature was cooled from 350°C to 200°C at a cooling rate of 10°C / min. A second heating was then performed from 200°C to 350°C at a heating rate of 10°C / min. The melting point was determined from the peak value of the melting curve generated during the second heating process.
[0173] Comparative Example 1
[0174] 40.25 kg of deionized water and 0.240 kg of methanol were added to a 174 L autoclave equipped with a stirrer, and the autoclave was thoroughly purged with nitrogen under vacuum. Afterward, the autoclave was degassed under vacuum, and 40.25 kg of HFP was added to the vacuum-sealed autoclave, which was then heated to 32.0 °C. Next, TFE was added until the internal pressure of the autoclave reached 0.938 MPa. Then, 0.31 kg of 8% by mass di(ω-hydroperfluorohexanoyl) peroxide solution (hereinafter referred to as DHP) was added to the autoclave to begin polymerization. The internal pressure of the autoclave at the start of polymerization was set to 0.938 MPa, and this pressure was maintained by continuously adding TFE. 0.240 kg of methanol was added 1.5 hours after the start of polymerization. Two hours after the start of polymerization, 0.31 kg of DHP was added, and four hours later, with the internal pressure reduced by 0.001 MPa. Six hours later, 0.24 kg of DHP was added, with the internal pressure reduced by 0.001 MPa. Thereafter, 0.07 kg of DHP was added every two hours until the reaction was complete.
[0175] Additionally, 0.240 kg of methanol was added to the autoclave at TFE addition levels of 6.0 kg and 18.1 kg, respectively. The polymerization was then terminated when the TFE addition reached 40.25 kg. After polymerization, unreacted TFE and HFP were released, yielding a wet powder. This wet powder was then washed with pure water and dried at 150°C for 10 hours to obtain 46.2 kg of dry powder.
[0176] The obtained powder was melt-extruded at 370°C using a screw extruder (trade name: PCM46, manufactured by Chibei Co., Ltd.) to obtain copolymer granules. The HFP and PPVE contents of the obtained granules were determined using the method described above. The results are shown in Table 3.
[0177] The obtained granules were degassed in an electric furnace at 200°C for 8 hours, then placed in a VVD-30 vacuum vibratory reactor (manufactured by Okawahara Seisakusho Co., Ltd.), and heated to 200°C. After evacuation, F2 gas diluted to 20% by volume with N2 gas was introduced to atmospheric pressure. 0.5 hours after the introduction of F2 gas, a temporary vacuum was applied, and F2 gas was introduced again. This process was repeated 0.5 hours later, followed by another vacuum and introduction of F2 gas. This process of introducing F2 gas and evacuating the vacuum was repeated every hour, and the reaction was carried out at 200°C for 8 hours. After the reaction, the reactor was completely replaced with N2 gas to terminate the fluorination reaction, yielding granules. Various physical properties of the obtained granules were measured using the above method. The results are shown in Table 3.
[0178] Comparative Example 2
[0179] 40.25 kg of deionized water and 0.085 kg of methanol were added to a 174 L autoclave equipped with a stirrer, and the autoclave was thoroughly purged with nitrogen under vacuum. Then, the autoclave was degassed under vacuum, and 40.25 kg of HFP was added to the vacuum-sealed autoclave. The autoclave was then heated to 30.0 °C. Next, TFE was added until the internal pressure of the autoclave reached 0.906 MPa. Then, 0.63 kg of 8% by mass di(ω-hydroperfluorohexanoyl) peroxide solution (hereinafter referred to as DHP) was added to the autoclave to begin polymerization. The internal pressure of the autoclave at the start of polymerization was set to 0.906 MPa, and this pressure was maintained by continuously adding TFE. 0.085 kg of methanol was added 1.5 hours after the start of polymerization. Two hours after the start of polymerization, 0.63 kg of DHP was added, and four hours later, with the internal pressure reduced by 0.001 MPa. Six hours later, 0.48 kg of DHP was added, with the internal pressure reduced by 0.001 MPa each time. Thereafter, 0.13 kg of DHP was added every two hours until the reaction was complete, with the internal pressure reduced by 0.001 MPa each time.
[0180] Additionally, 0.085 kg of methanol was added to the autoclave at TFE addition levels of 6.0 kg and 18.1 kg, respectively. The polymerization was then terminated when the TFE addition reached 40.25 kg. After polymerization, unreacted TFE and HFP were released, yielding a wet powder. This wet powder was then washed with pure water and dried at 150°C for 10 hours to obtain 45.7 kg of dry powder.
[0181] The obtained powder was melt-extruded at 370°C using a screw extruder (trade name: PCM46, manufactured by Chibei Co., Ltd.) to obtain copolymer granules. The HFP and PPVE contents of the obtained granules were determined using the method described above. The results are shown in Table 3.
[0182] The obtained granules were fluorinated in the same manner as in Comparative Example 1. Using the obtained granules, various physical properties were determined by the method described above. The results are shown in Table 3.
[0183] Comparative Example 3
[0184] The amount of methanol added before polymerization was changed to 0.106 kg, and the amount of methanol added in batches after polymerization began was also changed to 0.106 kg each time. The set pressure inside the autoclave before and after polymerization was changed to 0.923 MPa. Otherwise, copolymer granules were obtained in the same manner as in Comparative Example 1. The HFP and PPVE contents of the obtained granules were determined using the above method. The results are shown in Table 3.
[0185] The obtained granules were fluorinated in the same manner as in Comparative Example 1. Using the obtained granules, various physical properties were determined by the method described above. The results are shown in Table 3.
[0186] Comparative Example 4
[0187] 945g of deionized water was added to a 4L autoclave equipped with a stirrer, and the autoclave was thoroughly purged with nitrogen. Then, the autoclave was degassed under vacuum, and 945g of HFP was added to the vacuum-sealed autoclave. The autoclave was heated to 32.0°C. Next, TFE was added until the internal pressure of the autoclave reached 0.938MPa. Then, 5.1g of 8% by mass di(ω-hydroperfluorohexanoyl) peroxide solution (hereinafter referred to as DHP) was added to the autoclave to begin polymerization. The internal pressure of the autoclave at the start of polymerization was set to 0.938MPa, and this pressure was maintained by continuously adding TFE. 5.1g of DHP was added after 2 hours, 4 hours, and 4.0g after 6 hours. Thereafter, 1.1g of DHP was added every 2 hours until the reaction was complete.
[0188] Furthermore, polymerization was terminated when the additional TFE addition reached 380 g. After polymerization, unreacted TFE and HFP were released, yielding a wet powder. This wet powder was then washed with pure water, dried at 150°C for 10 hours, and then dried at 205°C for 24 hours, yielding 436 g of dry powder. The HFP and PPVE contents of the obtained powder were determined using the method described above. The results are shown in Table 3.
[0189] The obtained powder was placed in a portable TVS1 type reactor (manufactured by Pressure Glass Industry Co., Ltd.) and heated to 200°C. After evacuation, F2 gas diluted to 20% by volume with N2 gas was introduced to atmospheric pressure. 0.5 hours after the introduction of F2 gas, a temporary vacuum was applied, and F2 gas was introduced again. Then, after another 0.5 hours, a vacuum was applied again, and F2 gas was introduced again. This process of introducing F2 gas and evacuating the vacuum was repeated every hour, and the reaction was carried out at 200°C for 8 hours. After the reaction was completed, the reactor was completely replaced with N2 gas to stop the fluorination reaction, yielding the powder. Various physical properties of the obtained powder were determined using the above method. The results are shown in Table 3.
[0190] Comparative Example 5
[0191] 40.25 kg of deionized water and 0.066 kg of methanol were added to a 174 L autoclave equipped with a stirrer, and the autoclave was thoroughly purged with nitrogen under vacuum. Afterward, the autoclave was degassed under vacuum, and 40.25 kg of HFP and 0.32 kg of PPVE were added to the vacuum-sealed autoclave. The autoclave was then heated to 32.0 °C. Next, TFE was added until the internal pressure of the autoclave reached 0.928 MPa. Then, 0.31 kg of 8% by mass di(ω-hydroperfluorohexanoyl) peroxide solution (hereinafter referred to as DHP) was added to the autoclave to begin polymerization. The internal pressure of the autoclave at the start of polymerization was set to 0.928 MPa, and this pressure was maintained by continuously adding TFE. 0.066 kg of methanol was added 1.5 hours after the start of polymerization. Two hours after the start of polymerization, 0.31 kg of DHP was added, and four hours later, with the internal pressure reduced by 0.001 MPa. Six hours later, 0.24 kg of DHP was added, with the internal pressure reduced by 0.001 MPa. Thereafter, 0.07 kg of DHP was added every two hours until the reaction was complete.
[0192] It should be noted that 0.11 kg of PPVE was added at the points when the TFE addition reached 8.1 kg, 16.2 kg, and 24.3 kg, respectively. Additionally, 0.066 kg of methanol was added to the autoclave at the points when the TFE addition reached 6.0 kg and 18.1 kg, respectively. The polymerization was terminated when the TFE addition reached 40.25 kg. After polymerization, unreacted TFE and HFP were released, yielding a wet powder. This wet powder was then washed with pure water and dried at 150°C for 10 hours to obtain 47.0 kg of dry powder.
[0193] The obtained powder was melt-extruded at 370°C using a screw extruder (trade name: PCM46, manufactured by Chibei Co., Ltd.) to obtain copolymer granules. The HFP and PPVE contents of the obtained granules were determined using the method described above. The results are shown in Table 3.
[0194] The obtained granules were fluorinated in the same manner as in Comparative Example 1. Using the obtained granules, various physical properties were determined by the method described above. The results are shown in Table 3.
[0195] Comparative Example 6
[0196] The amount of methanol added before polymerization was changed to 0.099 kg, and the amount of methanol added in batches after polymerization began was also changed to 0.099 kg each time. The set pressure inside the autoclave before and after polymerization was changed to 0.932 MPa. Otherwise, copolymer granules were obtained in the same manner as in Comparative Example 1. The obtained granules were used without fluorination, and various physical properties were measured using the above method. The results are shown in Table 3.
[0197] Example 1
[0198] The amount of methanol added before polymerization was changed to 0.051 kg, and the amount of methanol added in batches after polymerization began was also changed to 0.051 kg each time. The set pressure inside the autoclave before and after polymerization was changed to 0.947 MPa. Otherwise, copolymer granules were obtained in the same manner as in Comparative Example 1. The HFP and PPVE contents of the obtained granules were determined using the above method. The results are shown in Table 3.
[0199] The obtained granules were fluorinated in the same manner as in Comparative Example 1. Using the obtained granules, various physical properties were determined by the method described above. The results are shown in Table 3.
[0200] Example 2
[0201] The amount of methanol added before polymerization was changed to 0.112 kg, and the amount of methanol added in batches after polymerization began was also changed to 0.112 kg each time. The set pressure inside the autoclave before and after polymerization was changed to 0.938 MPa. Otherwise, copolymer granules were obtained in the same manner as in Comparative Example 1. The HFP and PPVE contents of the obtained granules were determined using the above method. The results are shown in Table 3.
[0202] The obtained granules were fluorinated in the same manner as in Comparative Example 1. Using the obtained granules, various physical properties were determined by the method described above. The results are shown in Table 3.
[0203] Example 3
[0204] The amount of methanol added before polymerization was changed to 0.124 kg, and the amount of methanol added in batches after polymerization began was also changed to 0.124 kg each time. The set pressure inside the autoclave before and after polymerization was changed to 0.928 MPa. Otherwise, copolymer granules were obtained in the same manner as in Comparative Example 1. The HFP and PPVE contents of the obtained granules were determined using the above method. The results are shown in Table 3.
[0205] The obtained granules were degassed in an electric furnace at 200°C for 72 hours, then placed in a VVD-30 vacuum vibratory reactor (manufactured by Okawahara Seisakusho Co., Ltd.), and heated to 120°C. After evacuation, F2 gas diluted to 20% by volume with N2 gas was introduced to atmospheric pressure. 0.5 hours after the introduction of F2 gas, a temporary vacuum was applied, and F2 gas was introduced again. This process was repeated 0.5 hours later, followed by another vacuum and introduction of F2 gas. This process of introducing F2 gas and evacuating the vacuum was repeated every hour, and the reaction was carried out at 120°C for 7 hours. After the reaction, the reactor was completely replaced with N2 gas to terminate the fluorination reaction, yielding granules. Various physical properties of the obtained granules were measured using the above method. The results are shown in Table 3.
[0206] [Table 3]
[0207] Table 3
[0208]
[0209] Table 3 shows "Other (number / C10)" 6 The notation “)” indicates the total number of -COOCH3, -CF=CF2, and -CONH2. The notation “<9” in Table 3 means the number (total) of -CF2H groups is less than 9. The notation “<6” in Table 3 means the number (total) of the target functional group is less than 6. The notation “ND” in Table 3 indicates a peak for which quantification could not be achieved.
[0210] Next, the obtained granules were used to evaluate the following properties. The results are shown in Table 4.
[0211] (Abrasion test)
[0212] Using a granulation and hot-press molding machine, sheet-shaped test pieces with a thickness of approximately 0.2 mm were prepared, from which 10 cm × 10 cm test pieces were cut. The prepared test pieces were fixed on the test bench of a Tiber abrasion testing machine (No. 101 Special Type Tiber Abrasion Testing Machine, manufactured by Yasuda Seiki Co., Ltd.). Abrasion tests were conducted using the Tiber abrasion testing machine under the following conditions: temperature 25°C, load 500 g, abrasion wheel CS-10 (grinding with #240 abrasive paper for 20 revolutions), and rotation speed 60 rpm. The weight of the test piece was measured after 1000 revolutions, and the same test piece was further tested after 10000 revolutions, and the weight of the test piece was measured again. The amount of abrasion was calculated using the following formula.
[0213] Wear amount (mg) = M1 - M2
[0214] M1: Weight of the test piece after 1000 revolutions (mg)
[0215] M2: Weight of the test piece (mg) after 10,000 revolutions.
[0216] (Ozone Exposure Test)
[0217] Fluorinated copolymers were compressed at 350°C and 0.5 MPa to produce 1 mm thick sheets, from which 10 × 20 mm samples were cut as ozone exposure test specimens. Ozone gas (ozone / oxygen = 10 / 90 volume%) generated by an ozone generator (trade name: SGX-A11MN (modified), manufactured by Sumitomo Seiki Kogyo Co., Ltd.) was connected to a PFA container filled with ion-exchanged water. Water vapor was added to the ozone gas while bubbling in the ion-exchanged water, and the gas was passed through the PFA tank containing the specimen at 0.7 L / min at room temperature, exposing the specimen to the moist ozone gas. After 135 days from the start of exposure, the specimens were removed, and the surface was gently rinsed with ion-exchanged water. A transmission optical microscope was used to observe the portion from 5 μm to 200 μm below the specimen surface at 100x magnification, and the images were taken along with standard measurements. Measurements were taken at 1 mm depth per 1 mm of the specimen surface. 2 The number of cracks with a length of 10 μm or more.
[0218] The evaluation will be conducted according to the following criteria.
[0219] ○: The number of cracks is less than 10
[0220] ×: More than 10 cracks
[0221] (Carbon dioxide permeability coefficient)
[0222] A sheet-like test piece with a thickness of approximately 0.1 mm was prepared using granulation and a hot press molding machine. Using the obtained test piece, the carbon dioxide transmittance was measured using a differential pressure gas transmittance meter (L100-5000 type gas transmittance meter, manufactured by Systech Illinois) according to the method described in JIS K7126-1:2006. The transmittance area was found to be 50.24 cm². 2 The carbon dioxide transmittance was measured at a test temperature of 70℃ and a test humidity of 0%RH. Using the obtained carbon dioxide transmittance and the thickness of the test piece, the carbon dioxide transmittance coefficient was calculated using the following formula.
[0223] Carbon dioxide permeability (cm) 3 ·mm / (m 2 ·24h·atm))=GTR×d
[0224] GTR: Carbon dioxide transmittance (cm) 3 / (m 2 ·24h·atm))
[0225] d: Thickness of the test piece (mm)
[0226] (75℃ load deflection)
[0227] Using granulation and a hot press, sheet-like test pieces with a thickness of approximately 2.4 mm were prepared. 80 × 10 mm test pieces were cut from these pieces and heated in an electric furnace at 75°C for 20 hours. In addition to using the obtained test pieces, tests were conducted according to the method described in JIS K-K7191-1 using a heat distortion tester (manufactured by Yasuda Seiki Co., Ltd.) under the following conditions: test temperature 30°C–150°C, heating rate 120°C / hour, bending stress 1.8 MPa, and flatwise method. The load deflection was calculated using the following formula. Sheets with low load deflection at 75°C exhibit excellent rigidity at the high temperature of 75°C.
[0228] Load-induced deflection (%) = a2 / a1 × 100
[0229] a1: Thickness of the test piece before the test (mm)
[0230] a2: Deflection at 75℃ (mm)
[0231] (Tensile creep test)
[0232] Tensile creep strain was determined using a Hitachi High-Tech TMA-7100. Sheets approximately 0.1 mm thick were prepared using a granulator and thermoforming machine. Samples 2 mm wide and 22 mm long were then fabricated from these sheets. The samples were mounted in the measuring fixture with a 10 mm gap between the clamps. A cross-sectional load of 4.49 N / mm² was applied to the samples.2 The sample was subjected to a load at 110°C, and the displacement (mm) of its length was measured from 90 minutes to 900 minutes after the start of the test. The ratio of the displacement (mm) to the initial sample length (10mm) was calculated (tensile creep strain (%)). Samples with low tensile creep strain (%) measured at 110°C for 900 minutes do not easily elongate even under prolonged tensile loads in high-temperature environments, demonstrating excellent high-temperature tensile creep resistance (110°C).
[0233] (Tensile strength after 30,000 cycles)
[0234] The tensile strength after 30,000 cycles was determined using a Shimadzu MMT-250NV-10 fatigue testing machine. A pellet approximately 2.4 mm thick was prepared using a granulation and thermoforming machine. A dumbbell-shaped sample (2.4 mm thickness, 5.0 mm width, and 22 mm measuring section length) was fabricated using ASTM D1708 micro-dumbbells. The sample was mounted in the testing fixture, which was then placed in a 110°C constant temperature bath with the sample mounted. Uniaxial tension was repeatedly applied at a stroke of 0.2 mm and a frequency of 100 Hz, and the tensile strength (tensile strength at a stroke of +0.2 mm, unit: N) was measured for each tension.
[0235] The sheet with high tensile strength after 30,000 cycles maintains high tensile strength even after being subjected to 30,000 loads, and has excellent durability under repeated loads (110°C).
[0236] (Immersion test in hydrogen peroxide water)
[0237] Using granulation and a hot press molding machine, sheets with a thickness of approximately 0.2 mm were made, and test sheets with a square diameter of 15 mm were prepared. Ten test sheets and 15 g of 3% (w / w) hydrogen peroxide aqueous solution were placed in a 50 mL polypropylene bottle. The mixture was heated at 95°C for 20 hours and then cooled to room temperature. The test sheets were removed from the hydrogen peroxide aqueous solution, and TISAB solution (10) (manufactured by Kanto Chemical Co., Ltd.) was added to the remaining hydrogen peroxide aqueous solution. The fluoride ion concentration in the resulting hydrogen peroxide aqueous solution was measured using a fluoride ion meter. The fluoride ion concentration per unit weight of sheet (dissolved fluoride ion concentration) was calculated from the measured values according to the following formula.
[0238] Dissolved fluoride ion concentration (ppm) = Measured value (ppm) × Volume of hydrogen peroxide aqueous solution (g) / Weight of test piece (g)
[0239] (Membrane forming properties)
[0240] use An extruder (manufactured by Imoto Manufacturing Co., Ltd.) and a T-die are used to shape the granules into a film. The extrusion molding conditions are as follows.
[0241] a) Winding speed: 0.4 m / min
[0242] b) Roller temperature: 120℃
[0243] c) Membrane width: 70mm
[0244] d) Thickness: 0.25mm
[0245] e) Extrusion conditions:
[0246] • Single-screw extrusion molding machine with a barrel shaft diameter of 14mm and an L / D ratio of 20
[0247] Extruder set temperatures: Barrel section C-1 (330℃), Barrel section C-2 (350℃), Barrel section C-3 (365℃), T-die head (370℃)
[0248] Continue extruding the fluorinated copolymer until it is stably extruded from the molding machine. Next, by extruding the fluorinated copolymer, produce a film with a length of 5 m or more (70 mm wide) with a thickness of 0.25 mm. Cut a 4-5 m section from the end of the obtained film to prepare a test piece (1 m long, 70 mm wide) for measuring thickness variation. Measure the thickness at a total of three locations: the center point in the width direction at the end of the film and two locations 25 mm away from that center point in the width direction. Furthermore, measure the thickness at a total of nine locations: three center points spaced 25 cm apart from the center point at one end of the film towards the other end, and two locations 25 mm away from each center point in the width direction. Of the total 12 measurements, those with 1 or fewer measurements outside the ±10% range of 0.25 mm are designated as ○, and those with 2 or more measurements outside the ±10% range of 0.25 mm are designated as ×.
[0249] (Tube Formability)
[0250] use The extruder (manufactured by Tanabe Plastic Machinery) extrudes the granules to form a tube with an outer diameter of 10.0 mm and a wall thickness of 1.0 mm. The extrusion molding conditions are as follows.
[0251] a) Die head inner diameter: 25mm
[0252] b) Outer diameter of the spindle: 13mm
[0253] c) Inner diameter of the shaping mold: 10.5mm
[0254] d) Traction speed: 0.4 m / min
[0255] e) Outer diameter: 10.0mm
[0256] f) Wall thickness: 1.0mm
[0257] g) Extrusion conditions:
[0258] • Single-screw extrusion molding machine with a barrel shaft diameter of 30mm and an L / D ratio of 22
[0259] Extruder set temperatures: Barrel section C-1 (350℃), Barrel section C-2 (370℃), Barrel section C-3 (380℃), Head section H-1 (390℃), Die head section D-1 (390℃), Die head section D-2 (390℃)
[0260] The obtained tubes are observed and evaluated according to the following criteria. The appearance of the tubes is confirmed visually.
[0261] 〇: Good appearance
[0262] ×: The cross-section is not circular, and flatness or uneven thickness is observed, resulting in a poor appearance.
[0263] (Conditions for wire coating)
[0264] use A wire coating molding machine (manufactured by Tanabe Plastics Machinery Co., Ltd.) extrudes a fluorinated copolymer onto a copper conductor with a conductor diameter of 1.00 mm to obtain a coated wire at the following coating thickness. The wire coating extrusion molding conditions are as follows.
[0265] a) Core conductor: Conductor diameter 1.00mm
[0266] b) Coating thickness: 0.70mm
[0267] c) Diameter of the covered wire: 2.40mm
[0268] d) Wire pulling speed: 3m / minute
[0269] e) Extrusion conditions:
[0270] • Single-screw extrusion molding machine with a barrel shaft diameter of 30mm and an L / D ratio of 22
[0271] • Mold (inner diameter) / piece (outer diameter) = 24.0mm / 10.0mm
[0272] Extruder set temperatures: Barrel section C-1 (340℃), Barrel section C-2 (375℃), Barrel section C-3 (390℃), Head H (400℃), Die head D-1 (400℃), Die head D-2 (400℃). Core wire preheating is set to 80℃.
[0273] (Changes in outer diameter)
[0274] The outer diameter of the coated wire was measured continuously for one hour using an outer diameter measuring instrument (Zumbach ODAC18XY). The outer diameter value was rounded to three decimal places from the maximum deviation from the specified outer diameter value (2.40 mm), thus determining the variation in outer diameter. The ratio of the absolute value of the difference between the specified outer diameter and the variation in outer diameter to the specified outer diameter (2.40 mm) (the rate of change in outer diameter) was calculated and evaluated according to the following criteria.
[0275] (Rate of change in outer diameter (%)) = |(Change in outer diameter) - (Specified outer diameter)| / (Specified outer diameter) × 100
[0276] ±1%: The variation rate of the outer diameter is less than 1%.
[0277] ±2%: The rate of change in outer diameter exceeds 1% but is less than 2%.
[0278] ×: The rate of change in outer diameter exceeds 2%.
[0279]
Claims
1. A fluorinated copolymer, comprising tetrafluoroethylene units, hexafluoropropylene units, and fluorinated (alkyl vinyl ether) units, wherein, Fluorinated (alkyl vinyl ethers) are at least one selected from the group consisting of perfluorinated (methyl vinyl ether), perfluorinated (ethyl vinyl ether), and perfluorinated (propyl vinyl ether). The content of hexafluoropropylene units relative to all monomer units is 11.5%–12.5% by mass. The content of fluorinated (alkyl vinyl ether) units is 0–0.5% by mass relative to all monomer units. The content of tetrafluoroethylene units relative to all monomer units is 87.0%–88.5% by mass. The melt flow rate, measured as the mass of polymer flowing out of a die with an inner diameter of 2 mm and a length of 8 mm every 10 minutes at 372°C and a load of 5 kg, was 0.8 g / 10 min to 4.0 g / 10 min. the total number of -CF2H, carbonyl-containing end groups, -CF=CF2, and -CH2OH is 50 or less per 10 6 main chain carbon atoms.
2. The fluorocopolymer of claim 1, wherein, The content of fluorinated (alkyl vinyl ether) units is 0 to 0.1% by mass relative to all monomer units.
3. The fluorinated copolymer as described in claim 1 or 2, wherein, The melt flow rate, measured as the mass of polymer flowing out of a die with an inner diameter of 2 mm and a length of 8 mm every 10 minutes at 372°C and a load of 5 kg, was 1.0 g / 10 min to 3.2 g / 10 min.
4. The fluorinated copolymer as described in claim 1 or 2, wherein, The fluorinated (alkyl vinyl ether) unit is a perfluorinated (propyl vinyl ether) unit.
5. An extruded article comprising the fluorinated copolymer according to any one of claims 1 to 4.
6. A transfer molded article comprising any one of claims 1 to 4.
7. A coated wire having a coating layer comprising a fluorinated copolymer according to any one of claims 1 to 4.
8. A molded article comprising the fluorinated copolymer according to any one of claims 1 to 4, wherein, The molded body is a bottle, bag, tube, film, or wire cover.
Citation Information
Patent Citations
Multilayer polymer structure
JP2001501551A
Layered body and tube
WO2019220850A1
Sealing material
CN103946250A
Tetrafluoroethylene / hexafluoropropylene copolymer, and electric wire
CN105980426A
